KOHESI DAN KOHERENSI DALAM ARTIKEL ILMIAH POPULER DI MEDIA MASSA - Ade Ismail (Jurnal Bilingual, 2021)
Writing is essentially describing ideas both in journals and in the mass media. This skill is considered as a method of binding knowledge and educational insights, including writing popular scientific papers in the mass media. This study aims to examine the cohesiveness and coherence of texts in the mass media. The data from this study were 5 (five) articles in one of the mass media published in 2017. This study used a descriptive qualitative method, meanwhile, the data was analyzed using the Miles and Huberman model. The results showed that to establish cohesion and coherence in the text, the writers had used conjunctions and punctuation well. However, in terms of coherence, they are still hampered in the process of assembling and sorting ideas that are acceptable in the context of the text.